Review of the Oriental species of the genus Brachycerocoris Costa, 1863 (Hemiptera: Pentatomoidea: Pentatomidae: Podopinae s.l.) with description of two new species - Salini, S.; Roca-Cusachs, M. (Zootaxa, 2021)
The Oriental species belonging to genus Brachycerocoris Costa, 1863 (Hemiptera: Pentatomoidea: Pentatomidae: Podopinae s.l.) are revised with description of two new species, B. petrii sp. nov. and B. davidii sp. nov. from India and Philippines respectively. Brachycerocoris camelus Costa, 1863 is diagnosed and illustrated for female genitalia and B. dromedarius (Vollenhoven, 1863) is diagnosed and illustrated for both male and female genitalia. Additionally, host record, bionomics of B. petrii sp. nov. and a key to the Oriental species are provided.